Enhancement Ability to Write Complex Procedure Texts through Quantum Writing Method Students of Class XI SMA 3 Sidrap. - Manda, Ibrahim; Sadapotto, Andi; Buhari, Buhari; N, Zulkifli; Hambing, Agus (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
Learning Language Indonesia in Senior High School 3 Sidrap Which is done by the Teacher does not yet show quality, so students feel fed up, and not enough active in learning, and student learning outcomes are still low. This research aims to know the performance model And know increasing learning outcomes through the application of the Quantum method of Writing. Study This uses the method of Study Class Action ( PTK ) which is carried out in two cycles. Each cycle consists of one meeting, and each cycle consists of four stages viz planning, implementation, observation, And reflection. Data results study in getting by using student activity observation sheets as well tests. The research results obtained are an increase in value significant from cycle I to cycle II. Still, students in cycle I are still in the less category, in cycle II are in a good and very good position. This clearly shows a difference. In cycle I there are only eight students who completed KKM, while in cycle II 29 students Already completed KKM. With thereby, 72.4% of student experience enhancement from cycle I to cycle II.